Secure Data Hiding in Encrypted Video Using SVD - Akilashri, P.S.S; Kannan, M (International Journal of Computer Sciences and Engineering, 2025)
Video data hiding is a very Abstract – Video data hiding is very important research topic. Security of information is major concern of information technology and communication. This paper introduces svd and Least Significant bit substitution technique for hiding data in video file. In this paper data hiding a form of cryptography embeds data into digital media for the purpose of identification, annotation. These algorithms are a basic algorithm of encryption and decryption for data hiding. The framework is tested by all kind of videos such as .mp4, .3gp, .avi etc., and gets successful output for all video data hiding process. The three components Red, Green, Blue of (RGB) space are utilized by this scheme to embed watermark into the cover image. Specifically the combinations of Singular Value Decomposition (SVD) of Blue channel are used to embed the data hiding. The singular values of wavelet subband coefficients of Blue channel are use in different scaling factors to embed the singular values of the data. The SVD increases the security, robustness and imperceptibility of the scheme. The proposed scheme used by security, while hiding the video to provide security for encrypts and decrypt process. The simulation results show that the process of hiding the video by security